Assessment of changes in the threadfin bream species composition using Markov chain - Vivekanandan, E; Venugopalan, R; Ramadoss, P (Indian Journal of Fisheries, 2011)
The threadfin bream landings in the Chennai Fisheries Harbour consistentlydeclined from 5450 t in 1994 to 2406 t in '98. The catch rate also declined from22.6 kg/trawl hour in '90 to 2.3 kg/h in '98. Markovian model is employed toassess the changes in species dominance over the 15 year period. Transitionprobabilities as well as the steady state probabilities are worked out separatelyfor four species of threadfin breams. It was found that the probability of dominanceof Nemipterus japonicus has decreased, indicating a major shift in thespecies composition of the threadfin breams. The possibility of short term predictionon the species dominance pattern by employing Markovian model isdemonstrated.